Job-related factors on employee’s productivity in workplace: a case study among nurses at Putra Specialist Hospital, Melaka / Nur Muhammad Yassin Abd Manap - Abd Manap, Nur Muhammad Yassin (Faculty of Administrative Science and Policy Studies, 2013)
According to Gronroos and Ojasalo (2004) productivity is the effectiveness of inputs are transformed into outputs which are goods or services. It means that, it measures how effective and efficiently the inputs resources, such as labour and capital, are being used to produce output. It is also about the relationship between the resources consumed to generate the products or services and the quality products or services that satisfy human needs. Higher productivity means achieving more with the same or lesser amount of input resources. Increase in productivity will lead to benefits such as higher standard of living, enanced competitiveness and better quality of life. As noted by Paul Krugman (1994), the ability of country ability to raise its output per worker will improve its standard of living. Productivity is the key word in raising competitiveness and consequently the prosperity of a nation. It is responsible for the continued growth of the important sectors of the economy.